High Fat Diet and In Utero Exposure to Maternal Obesity Disrupts Circadian Rhythm and Leads to Metabolic Programming of Liver in Rat Offspring - Borengasser, Sarah J. (Public Library of Science, 2014)
The risk of obesity in adulthood is subject to programming beginning at conception. In animal models, exposure to maternal obesity and high fat diets influences the risk of obesity in the offspring. Among other long-term changes, offspring from obese rats develop hyperinsulinemia, hepatic steatosis, and lipogenic gene expression in the liver at weaning. However, the precise underlying mechanisms leading to metabolic dysregulation in the offspring remains unclear. Using a rat model of overfeeding-induced obesity, we previously demonstrated that exposure to maternal obesity from pre-conception to birth, is sufficient to program increased obesity risk in the offspring. Offspring of obese rat dams gain greater body weight and fat mass when fed high fat diet (HFD) as compared to lean dam. Since, disruptions of diurnal circadian rhythm are known to detrimentally impact metabolically active tissues such as liver, we examined the hypothesis that maternal obesity leads to perturbations of core clock components and thus energy metabolism in offspring liver. Offspring from lean and obese dams were examined at post-natal day 35, following a short (2 wk) HFD challenge. Hepatic mRNA expression of circadian (CLOCK, BMAL1, REV-ERBα, CRY, PER) and metabolic (PPARα, SIRT1) genes were strongly suppressed in offspring exposed to both maternal obesity and HFD. Using a mathematical model, we identified two distinct biological mechanisms that modulate PPARα mRNA expression: i) decreased mRNA synthesis rates; and ii) increased non-specific mRNA degradation rate. Moreover, our findings demonstrate that changes in PPARα transcription were associated with epigenomic alterations in H3K4me3 and H3K27me3 histone marks near the PPARα transcription start site. Our findings indicated that offspring from obese rat dams have detrimental alternations to circadian machinery that may contribute to impaired liver metabolism in response to HFD, specifically via reduced PPARα expression prior to obesity development.